Minimum Sıcaklığı Tahmin İçin Bir Yöntem Ve Antalya'nın Minimum Sıcaklıklarına Uygulanması - Kılıç, Ahmet (Fen Bilimleri Enstitüsü, 1986)
Minimum hava sıcaklığı tahmini oldukça güç meteorolojik para metrelerden bir tanesidir. Bunun nedeni, minimum sıcaklığın bulut luluk ve rüzgar gibi ani değişmeler gösteren parametrelere fazlaca bağımlı olmasıdır. Bu çalışmada bulutluluk ve rüzgarın ayrıca tahmin edilmesini ge rektirmeyen bir kısa vade minimum sıcaklık tahmin yöntemi gelişti rilmiştir. Çalışmada uygulama için Antalya'nın minimum sıcaklıklarının se çilmesinin nedeni, Antalya'nın turfanda sebzecilikte Türkiye'de ilk sırayı alması ve bu sebeple minimum sıcaklıktaki değişmelerden en çok etkilenen il olmasıdır. Çalışmanın birinci bölümünde meteorolojide sıcaklık kavramları açıklanmış ve minimum sıcaklığın tahmin edilmesinin önemi belirtil miştir. ikinci bölümde Antalya ilinin tarım ve iklim özellikleri veril miştir. Üçüncü bölümde, sıcaklık tahmini açısından, atmosferde sıcaklı ğın diğer meteorolojik parametrelere bağlı olarak değişmesi incelen miş ve minimum sıcaklığın değişmesinde önceki güne ait maksimum sı caklığın, bulut örtüsünün ve rüzgarın etkileri gösterilmiştir. Çalışmanın dördüncü bölümünde, çevreden istasyona olan nem transferi esas alınarak, minimum sıcaklık tahmin yöntemi geliştiril miştir. Yöntem Antalya'nın minimum sıcaklıklarını tahmin için uygu lanmış ve başarılı sonuçlar alınmıştır. Son bölümde ise elde edilen sonuçlar verilmiştir.

Dynamic weather prediction models solve eomplex set of equations in order to forecast the circulation pattern days in advance. Some variables important for other usages, such as minimum and maximum temperature, precipitation type and amount are often not predicted directly or are predicted with insufficient accuracy by current dynamic weather prediction models. Minimum temperature is such a parameter that it presents some diffuculties to be estimated because of depending upon the conditions in the free atmosphere as well as at the earth's surface and varying rapidly when cloudiness and wind changed. This thesis deals with a short range minimum temperature forecast based on humidity transfer. The minimum temperatures at Antalya are selected for the application of this method due to the fact that the large amounts of early vegetables in Turkey are bred in Antalya and the Minimum temperature has to be known in advance for protecting the crops. If this method can be used operationally, it will be possible to save more money. In the first chapter, it is explained the reason for the prediction of the minimum temperature and general imformation is given about heat and temperatures in meteorology. The kinetic theory of gasses states that the temperature observed in a gas depends on the rate at which the molecules are moving about and is, in fact, proportional to the mean kinetic energy of the moving molecules. If the pressure remains constant, the heating of the gas will be accompanied by an increased kinetic energy. On the other hand, if no heat is added but the gas is compressed, the kinetic energy will also be increased by the compression, and the temperature of the gas will rise. Since heat is a form of energy, it is measurable in terms of temperature by thermometers. A number of air temperatures are used in meteorology. The two must common ones are the minimum and saximum temperature. Maximum temperature usually occurs several hours after the time of the highest sun, and the minimum usually just before sunrise. Air temperature, wet-bulb temperature, dew-point temperature, virtuol VI temperature, potential temperature, wet-bulb potential temperature and equivalent-potential temperature are some of the temperatures used in meteorology. The second chapter is concluded with the description of agricultural and climatological features of the province of Antalya. An important amount of early vegetables, such as tomato, pepper, French bean, cucumber, marrow, aubergine and water melon are grown in Antalya. In 1930, 22 800 ton of the 30 000 ton bananas, 237 000 ton of the 679 000 ton oranges and 735 000 ton of the 8 880 000 ton water-melons, tomatos, cucumbers, marrows, aubergines, peppers and French beans grown in Turkey. Antalya has the most of the greenhouses in Turkey. In the first half of 1985 Antalya has 29 560 dekars of the arable fields occupied by 30 500 greenhouses. Antalya has a "Mediterranean Climate" that is, a climate the coldest month of which will average well above freezinig. The summers are hot and winters are mild. Cold winters are not the rule. The warmest month is July with mean monthly temperature of 27.4°C and the maxima of 44.7°C. The coolest month is January. January mean temperature is 9.5°C. The minima is -4.6°C measured on February 5, 1950. The precipitation amounts in January, February, November and December are more than 100 kilograms per square meter and less than 10 kilograms per square meter. The mean annual "mean sea level" pressuere at Antalya is 1013.0 hPa. The monthly means are above the annual mean in the cool half of the year and below the annual mean in the warm half of the year. The mean annual wind speed is 3.1 meters per second. January and February more windy months. The third chapter of the thesis presents the details of the temperature changes in the atmosphere. The common air temperature measured in a shelter raised 1.5 m - 2.0 m above the ground varies with many factors. Among these, cloudiness and humidity of the air, nature of the earth's surface, the vertical lapse-rate of temperature, the surface pressure, and wind can be mentioned. r _ (8JL) __§_ z Cr and VII ,3T, g/C S 92 s dr (T) 1 +L/C -5- p dT gives an expression for the rate of change of temperature with height in a dry adiabatic and saturated adiabatic process respectively. The temperature change at the bottom of a layer may be expressed in a dry adiabatic process, 8 2Cd Tb " (1 + L_ )(Zıı _ Zh) 2Cp R In (Pb/ Pu) and in a saturated adiabatic process, dT The diurnal range is much influenced by cloud cover and wind speed. The clouds reduce the incoming radiation during the day and augment the downward radiation from the sky at night. Similarly, the mobility along the vertical of the air inceeases with the wind speed. On windy days, therefore, the heat exchange affects a deep layer of air, and the range of temperature at the surface is smaller then on calm days. The mobility does not only affect the exchange of heat but also the exchange of moisture. The amount of water vapor in the air exerts a noticeable influence. As a result, other conditions being the same, the night minimum temperature will be lower inhere the air column contains little moisture. Radiative transfer serves a mechanism for exchanging energy between the atmosphere and underlying surface and between different layers of the atmosphere, for that reason radiative transfer plays most important, role in the temperature changes.
A Method For Predicting Minimum Temperature And Its Application To Minimum Temperatures At Antalya
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1986
Thesis (Ph.D.) -- İstanbul Technical University, Institute of Science and Technology, 1986
Keywords: Antalya; meteorolojik parametreler; sıcaklık; iklim; Antalya; meteorological parameters; temperature; climate